NEFROPROTECTIVE EFFECTS OF ACTOVEGIN IN PATIENTS WITH DIABETIC NEPHROPATHY - І.І. Topchii; Y.Y. Yakymenko; P.S. Semenovykh; V.Yu. Galchinskaya; N.V. Yefimova (Ukrainian Journal of Nephrology and Dialysis, 2017)
Apoptosis, programmed cell death, regarded as one of the main mechanisms of glomerulosclerosis in diabetic nephropathy (DN).The aim of the present researchto study the effects of actovegin on cell apoptosis in patients with DN. Materials and methods: we examined 80 type 2 diabetic patients with DN I - IVstages and 10 healthy subjects. CD95+cells number was evaluated by indirect immunohis tochemistry.Results: CD95+ - cells number in the peripheral blood of patients with DN was significantly higher than in healthy donors. The additional actovegin treatment was accompanied by a significant decrease of the investigated parameter when compared with the base therapy.